The green home concept - acceptability and development problems - A. Alias,; T.K. Sin,; W.N.A.W.A Aziz, (Penerbit UKM, 2010)
People nowadays are more concerned about the environment since they know the effect of pollution to the environment and to human’s health. The conventional homes used up large amounts of power and produced large amount of carbon dioxides annually. Therefore, conventional homes are one of the sources of global warming. Conventional homes also polluted the environment. Green Home Concept is an effort made to reduce the impacts of conventional homes. Green home is a concept whereby a home is created to use less energy, water and natural resources, to provide good air quality and comfort, to generate less wastage, and can be considered as a sustainable development that improve the homeowners’ lifestyle. It is still a new trend in Malaysia housing development scene. This research focuses on the people’s acceptability and development problems that occur when developing green home by adopting case study and structural interviews methods. Questionnaire has also been applied to ascertain the Malaysian homeowners’ acceptability towards this new development concept. This research has also highlighted the concept and designs of green home in Malaysia. The findings reveal that uncertainty on people acceptability towards green home and the price are the biggest problems faced by developers when developing green home.